2016
DOI: 10.13189/nn.2016.040103
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanostructured Objects by Thermal Vacuum Deposition of Ge Films onto (100)GaAs Substrates

Abstract: The technique of thermal vacuum deposition of Ge onto GaAs substrates has been used for obtaining nanocrystalline Ge films. Nanocrystalline character of the films is confirmed by atomic force microscopy of their surface and by the data of Raman light scattering. The most probable size of the nanocrystallites forming the films decreases monotonically with decreasing their thickness. And raise of the deposition temperature results in their enlargement. Electro conductivity of such films proves to be high enough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…B4C/Al respectively. It is confirmed that the grain size enlargement and film thickness increases of the investigated samples are Borblik et al (2016) proposed that the decreases in the film thickness result in decreases of all scales characteristics of the material surface relief. Luce et al (Luce n.d.) reported that AFM could be used to analyse different sizes and types of images surface topography with easy sample preparation that is started from the nano-or microscale of the magnetic thin films.…”
Section: Afm Pit Morphologysupporting
confidence: 64%
“…B4C/Al respectively. It is confirmed that the grain size enlargement and film thickness increases of the investigated samples are Borblik et al (2016) proposed that the decreases in the film thickness result in decreases of all scales characteristics of the material surface relief. Luce et al (Luce n.d.) reported that AFM could be used to analyse different sizes and types of images surface topography with easy sample preparation that is started from the nano-or microscale of the magnetic thin films.…”
Section: Afm Pit Morphologysupporting
confidence: 64%
“…Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface. Luce et al [20] reported the use of AFM to analyse sizes and other important characteristics for surface topography with ease in Materials 2021, 14 Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface.…”
Section: Discussionmentioning
confidence: 99%
“…Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface. Luce et al [20] reported the use of AFM to analyse sizes and other important characteristics for surface topography with ease in Materials 2021, 14 Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface. Luce et al [20] reported the use of AFM to analyse sizes and other important characteristics for surface topography with ease in Materials 2021, 14 Borblik et al [19] proposed that the decreases in the size of sample resulted in decreases in all characteristics of the material surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thin films kept decreasing all the grain's length as the root mean square because of the enlargement added particles time growth. Thus, the decrease in the film's thickness causes a decrease in the surface of the hybrid material characterisations [45].…”
Section: Metallographic Fe-sem and Afm Analysismentioning
confidence: 99%